Republic of Serbia : First Review Under the Stand-By Arrangement and Requests for Augmentation, Extension of the Arrangement, Rephasing of Purchases, Waiver of Applicability of End-March Performance Criterion and Modification of End-June Performance Criteria, and Financing Assurances Review; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents key findings of the First Review under the Stand-by Arrangement (SBA) for the Republic of Serbia. The banking system of Serbia has weathered the external shocks well, but credit is slowing sharply. To safeguard economic stability in this markedly deteriorated environment, the authorities have revised their strategy. IMF staff supports the authorities' request for an augmentation and extension of the SBA, a rephasing of purchases, and completion of the first program review and the financing assurances review.